Предмет: Математика,
автор: leizstrong
Упростиет выражение: 6(3а -b)-2(a-3b)
Ответы
Автор ответа:
0
=18а-6b-2a+18b=-8b
все гениальное просто
все гениальное просто
Автор ответа:
0
Спасибо большое, ноо ответ минут 8, да?
Автор ответа:
0
Решение:
6(3a-b)-2(a-3b=18a-6b-2a+6b=16a
Ответ: 16а
6(3a-b)-2(a-3b=18a-6b-2a+6b=16a
Ответ: 16а
Похожие вопросы
Предмет: Физика,
автор: galinakisaa1971
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: sejsembaevanargiz
Предмет: Математика,
автор: Аноним